Central Nervous System Involvement-Positive (CNSI+) in Consolidation/Maintenance Stage Is a Poor Prognostic Factor in Pediatric T-Cell Acute Lymphoblastic Leukemia (T-ALL): A Chinese Single-Center Report - Liu, Xiaoming; Zou, Yao; Guo, Ye; Chen, Yumei; Chen, Xiaojuan; Zhang, Li; Zhu, Xiaofan; Yang, Wenyu (Blood, 2024)
Background The incidence of central nervous system (CNS) leukemia is about 5-10% in pediatric T-cell acute lymphoblastic leukemia (T-ALL), often with poor prognosis. However, the effect of CNS involvement-positive (CNSI+) in different stages on the survival of T-ALL children has not been reported. This study is to determine the prognostic significance of CNSI+ in newly diagnosed pediatric T-ALL. Method Children with T-ALL of consecutive phase 2 Chinese Children's Leukemia/Cancer Group (CCL/CG) clinical trials (CCLG-2008 and CCCG-2015) from 2008.4 to 2020.10 at the Pediatric Hematology and Oncology Diagnosis and Treatment Center of the Blood Disease Hospital of the Chinese Academy of Medical Sciences (Institute of Hematology, Chinese Academy of Medical Sciences) were examined. Determination of CNSI+ was based on flow cytometry (FCM). CNSI+: Leukemia cells were detected in the cerebrospinal fluid (CSF) by FCM. CNSI-: Leukemia cells were not detected in the CSF by FCM. Clinical characteristics, diagnosis, treatment and prognosis were analyzed. Results In combined analysis of 185 evaluable T-ALL subjects (CCLG-2008: 84; CCCG-2015: 101), 44 were CNSI+ (23.8%), with 26 in the induction stage, 24 in the consolidation/maintenance stage and 5 in both induction and consolidation/maintenance stage (all of them were from CNSI- to CNSI+ again). Besides initial leukemia blasts in the bone marrow (BM) (P<0.05), initial platelet (P<0.1), and glucocorticoid sensitivity (P<0.01), clinical features, such as age, gender, initial white blood cell (WBC), initial hemoglobin (HB), karyotype, immunophenotype and BM MRD during treatment (by flow cytometry, FCM) showed no difference between CNSI+ and CNSI- groups. Furthermore, children with ETP-ALL (35/185) were more likely to have CNSI+ in the induction stage (7/35 in the induction stage and 2/35 in the consolidation/maintenance stage, P<0.05). And compared with CNSI+ children in the consolidation/maintenance stage, patients with CNSI+ in the induction stage tended to have higher levels of BM-MRD (P<0.05). A total of 47 of the 185 (25.4%) children had recurrence (CNSI+: 24, CNSI-: 23), and 44 of the 185 (23.7%) children died (CNSI+: 18, CNSI-: 26). Compared with the CNSI- children and the CNSI+ children in the induction stage, the CNSI+ children in the consolidation/maintenance stage had a significantly higher cumulative recurrence rate (CRR) (10-year-CRR: 76.8±9.1%, 35.4±10.8%, and 17.4±3.3% respectively, P<0.001), as well as a significantly lower overall survival (OS) rate (10-year-OS: 48.9±11.0%, 70.0±10.2%, and 80.7±3.4%, respectively, P<0.05). Moreover, Patients with CNSI+ over three-times had the worst prognosis compared with those of CNSI+ under three-times or CNSI- (10-year-OS: 46.2±15.8%, 61.3±8.7%, and 80.7±3.4%, respectively, P<0.05; 10-year-DFS:, 8.5±8.1%, 56.6±9.1%, and 82.6±3.3%, respectively, P<0.001). Univariate and multivariate analyses showed that CNSI+ in the consolidation/maintenance stage was an unfavorable prognostic factor to T-ALL children's survival. Initial high leukemic burden, low platelets, and ETP-ALL immunophenotype were factors that contribute to CNSI+ in the induction stage. CDKN2A/CEP9, SIL/TAL1, and CREBBP may be associated with the CNSI+ in consolidation/maintenance stage. Eighteen of the 185 (9.7%) children underwent hematopoietic stem cell transplantation (HSCT) (12 cases survived, 4 died, and 2 were lost to follow-up). Conclusion CNSI+ especially in the consolidation/maintenance stage was an independent poor prognostic factor in pediatric T-ALL. HSCT improved outcomes of T-ALL children partially, but hardly helpful the patients with CNSI+ over three times. Individualized treatment strategies containing combination of immunotherapy and targeted therapy besides chemotherapy may improve patients' outcomes. No relevant conflicts of interest to declare.